Colorectal cancer combination therapy using drug and gene co-delivered, targeted poly(ethylene glycol)-ε-poly(caprolactone) nanocarriers - Wang Z; Wei Y; Fang G; Hong D; An L; Jiao T; Shi Y; Zang A (Dove Medical Press, 2018)
Zhiyu Wang, Yaning Wei, Guotao Fang, Dan Hong, Lin An, Ting Jiao, Yan Shi, Aimin Zang Hebei Key Laboratory of Cancer Radiotherapy and Chemotherapy, Department of Medical Oncology, Affiliated Hospital of Hebei University, Baoding 071000, People’s Republic of China Purpose: Combination therapy is a promising strategy to treat cancer due to the synergistic effects. The drug and gene co-delivered systems attract more attention in the field of combination therapy. Materials and methods: In the present research, poly(ethylene glycol)-ε-poly(caprolactone) block copolymer was used for the co-loading of 5-fluorouracil (5-FU) and gene. The physicochemical characteristics, in vitro and in vivo anticancer, and gene transfection efficiency were tested on colon cancer cells and tumor-bearing mice. Results: 5-FU and gene co-loaded nanocarriers had a size of 145 nm. In vivo gene delivery results showed about 60% of gene-positive cells. Tumor volume of nanocarrier groups at day 21 was around 320 mm3, which is significantly smaller compared with free 5-FU group (852 mm3) and control group (1,059 mm3). The maximum 5-FU plasma concentration in nanocarrier groups (49 µg/mL) was significantly greater than free 5-FU (13 µg/mL). At 24 hours, drug level of nanocarrier groups was about 2.8 µg/mL compared with 0.02 µg/mL of free 5-FU. Conclusion: The resulting nanocarriers co-loaded with the anticancer drugs and genes could be considered as a promising nanomedicine for colorectal cancer therapy. Keywords: colorectal cancer, gene therapy, combination therapy, cytotoxicity, transfection efficiency